Trauma’s Impact on Oral Healthcare: A Biopsychosocial and Trauma-Informed Approach - Qingyang Xu; Jill A York; Shaoyu Yuan (Journal of the California Dental Association)
Objectives This study explores the profound impact of trauma on oral health through a biopsychosocial lens, emphasizing the necessity of incorporating Trauma-Informed Care (TIC) within dental practice. It addresses the gap in current dental care models by proposing a comprehensive approach that integrates dental and mental health care to enhance treatment outcomes for trauma survivors.Methods We reviewed literature across disciplines, including psychology, dentistry, and social work, to illustrate how trauma influences oral health. A multidisciplinary model, the Dental-Mental Model with a TIC focus, was proposed, highlighting the need for a community-based team approach in dental practices.Results Trauma, including Adverse Childhood Experiences (ACEs), significantly affects oral health outcomes, contributing to conditions such as bruxism, Temporomandibular Joint Disorder (TMJD), and periodontal disease. Current healthcare models fail to adequately address the biopsychosocial complexities presented by trauma survivors. The Dental-Mental Model emphasizes early detection, sensitivity training, and adherence to TIC principles, aiming to improve patient trust, reduce dental anxiety, and enhance oral health outcomes.Conclusions Integrating a trauma-informed, multidisciplinary approach in dental care significantly improves the therapeutic relationship and treatment outcomes for individuals with a history of trauma. This model not only addresses the biopsychosocial factors affecting oral health but also promotes a holistic approach to patient care.Clinical Significance This study underscores the critical need for trauma-informed practices in dentistry. By adopting a holistic, multidisciplinary approach, dental professionals can offer more compassionate and effective care, ultimately enhancing the oral and overall health of individuals with trauma histories.